Penggunaan E-learning Sevima Edlink : Kajian Persepsi Siswa - Sela Purnamawati; Ira Mahartika (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2023)
This research aimed at analyzing student perceptions in using sevima edlink on Mol concept material.  It was a descriptive quantitative research.  Purposive sampling technique was used in this research.  The samples of this research were 35 students of X IPA grade at Senior High School of Cendana Pekanbaru.  Questionnaire and interview techniques were used for collecting the data.  The results of this research showed that students’ perception of X IPA grade at Senior High School of Cendana Pekanbaru was in good category in using Sevima Edlink e-learning (77%).  The implications of this research were using Sevima Edlink e-learning could provide benefits and additional e-learning for teachers and students, adding new insights related to e-learning for students, using Sevima Edlink   e-learning could form good perceptions for students, and inputting for other researchers to use Sevima Edlink as an online learning media.Keywords: Students’ Perception, Sevima Edlink, Mol Concept